DEVELOPING AUTHENTIC ASSESSMENT FOR MECHANICAL ENGINEERING SUBJECT OF VOCATIONAL SCHOOL STUDENTS (ESP) AT SMK N 2 OF BENGKULU - Erlian Dwisnu (JOALL (Journal of Applied Linguistics and Literature), 2018)
This research was aimed to know the appropriate assessment, find out speaking’s authentic assessment material and find out the characteristics of authentic speaking assessment model for Mechanical Engineering of Vocational School. The type of research was Research and Development. This study was conducted in Mechanical Engineering subject at SMKN 2 Bengkulu City. The sample was taken from third class of Mechanical Engineering students. The data was collected by using a questionnaire. The result of the study showed that; first, the appropriate assessment for Mechanical Engineering students Section of Vocational School in SMK N 2 of Bengkulu city was Authentic Assessment. Second,  the researcher found 4 kinds of speaking’s authentic assessment for Mechanical Engineering. It can be clasified into role play, presentation, picture cued and debate. Third, the characteristics of authentic speaking assessment model for students and teachers of Mechanical Engineering at SMKN 2 of Bengkulu city were topic of assessment, social function  format, type of authentic assessment, instrument of authentic assessment, types of rating scale/rubric and times.